Does soil pyrogenic carbon determine plant functional traits in Amazon Basin forests? - Massi, Klécia G. [UNESP]; Bird, Michael; Marimon, Beatriz S.; Marimon, Ben Hur; Nogueira, Denis S.; Oliveira, Edmar A.; Phillips, Oliver L.; Quesada, Carlos A.; Andrade, Ana S.; Brienen, Roel J. W.; Camargo, José L. C.; Chave, Jerome; et al. (Springer Nature, 2017)
Amazon forests are fire-sensitive ecosystems and consequently fires affect forest structure and composition. For instance, the legacy of past fire regimes may persist through some species and traits that are found due to past fires. In this study, we tested for relationships between functional traits that are classically presented as the main components of plant ecological strategies and environmental filters related to climate and historical fires among permanent mature forest plots across the range of local and regional environmental gradients that occur in Amazonia. We used percentage surface soil pyrogenic carbon (PyC), a recalcitrant form of carbon that can persist for millennia in soils, as a novel indicator of historical fire in old-growth forests. Five out of the nine functional traits evaluated across all 378 species were correlated with some environmental variables. Although there is more PyC in Amazonian soils than previously reported, the percentage soil PyC indicated no detectable legacy effect of past fires on contemporary functional composition. More species with dry diaspores were found in drier and hotter environments. We also found higher wood density in trees from higher temperature sites. If Amazon forest past burnings were local and without distinguishable attributes of a widespread fire regime, then impacts on biodiversity would have been small and heterogeneous. Alternatively, sufficient time may have passed since the last fire to allow for species replacement. Regardless, as we failed to detect any impact of past fire on present forest functional composition, if our plots are representative then it suggests that mature Amazon forests lack a compositional legacy of past fire.
Keywords: Climatological water deficit; Elevation; Fire; Fruit type; Soil charcoal; Temperature; Wood density